The application design based on Mobile Assisted Language Learning (Mall) to improve reading comprehension - Yogi Widyawati; Elitaria Siregar; Iwan Sonjaya (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2024)
Mobile learning has become increasingly prevalent in the education sector as smartphones are now part of everyday life. This study focuses on designing a mobile application to enhance the reading comprehension skills of students at Politeknik Negeri Jakarta (PNJ). Mobile learning offers students the flexibility to access learning materials anytime and anywhere, overcoming the limitations of classroom teaching hours. The research aims to develop a prototype of a Mobile Assisted Language Learning (MALL) application for Android smartphones, specifically tailored to assist students in preparing for the reading comprehension section of the TOEIC (Test of English for International Communication) test. The methodology involves analyzing the needs of PNJ students through surveys and interviews to identify their challenges in learning English, particularly in reading comprehension. Based on the findings, a prototype application was designed using iterative development processes, integrating features such as interactive reading exercises, real-time feedback, and progress tracking. The prototype was tested with final-year students to evaluate its effectiveness. The results indicate that the application significantly improves students' reading comprehension skills, as evidenced by higher practice scores and positive user feedback. The findings highlight the potential of MALL in bridging the gap in practice opportunities and limited classroom learning time.This research recommends further development of the application to include other sections of the TOEIC test, such as listening comprehension, and the integration of gamified features to enhance user engagement. Additionally, collaboration with vocational educators is suggested to ensure the content aligns with industry needs and language proficiency standards.